El lenguaje y la eficiencia de las organizaciones - Vázquez-Gómez, Rosa-Adriana (Hospitalidad ESDAI, 2005)
La invasión y rapidez de los cambios tecnológicos en todos los órdenes de la vida social y económica, y su empleo para hacer eficiente el trabajo en las empresas ha exaltado al lenguaje oral y escrito como la herramienta por excelencia para que aquéllas puedan cumplir con sus objetivos organizacionales. La atención a este recurso insustituible de la comunicación humana tiene que ver con el auge de la educación de corte constructivista. Ésta tiene por fundamento la autonomía del educando, sobre la base de lo que éste sabe y es capaz de desarrollar. El lenguaje verbal constituye la premisa de la construcción del conocimiento. Las universidades han hecho eco de esta tendencia y ahora la currícula da espacio a aquellas materias que propician el ejercicio de la reflexión y la expresión.

Invasive and swift technological changes in every order of social and economic life, and the use of such changes to increase work efficiency in companies has praised spoken and written language as the outstanding tool allowing enterprises to fulfill their institutional objectives. Attention to this irreplaceable resource, human communication, has to do with the boom of constructivism oriented education. This has a foundation student's autonomy, upon the basis of what student knows and is able to develop. Verbal language is a premise to knowledge construction. Universities have echoed this trend and currently their curricula allow for those academic subjects promoting the exertion of reflection and expression.

New consumer's attitudes and life styles result in changes in the food industry and in self-service store business. Today, preserved and processed foods are a fundamental component in the diet, mainly for urban population. There is a new way of selecting menus both in homes and restaurant industry, supporting the development of a processed food industry, known as convenience foods, incorporating a technology that allows an easier handling both in their preparation and their consumption. Thus, there are cooked and pre-cooked foods. The higher market presence of this type of foods is due, among other factors, to a fuller integration of women in the labor world. The most noticeable consumption trend for this type of foods has its origin in Europe and the United States. There is already a clear leaning in Mexico towards this type of consumption, mainly in urban areas. One of the main reasons for this is its convenience, together with other factors (flavor, price and ease for microwave warming up). Other advantages include their long shelf life and their easy consumption. Shortcomings include difficulty to identify ingredient quantity and quality.
Language and organization efficiency.
La nueva paradoja -- La enseñanza de la lengua -- El enfoque comunicativo en la enseñanza de la lengua -- De la oración al texto El lenguaje en las organizaciones -- Las situaciones de comunicación en las empresas -- El enfoque comunicativo en las organizaciones
La nueva paradoja -- La enseñanza de la lengua -- El enfoque comunicativo en la enseñanza de la lengua -- De la oración al texto -- El lenguaje en las organizaciones -- Las situaciones de comunicación en las empresas -- El enfoque comunicativo en las organizaciones
Keywords: Usos y costumbres; Rendimiento industrial; Comunicación; Constructivismo (Educación); Autonomía; Comunicación escrita; Innovaciones tecnológicas; Comunicación oral; HUMANIDADES Y CIENCIAS DE LA CONDUCTA; Administración de Instituciones; Humanidades